Integrating Islamic Legal Literacy In Environmental Sustainability: The An-Nadzir Community Practices in Gowa, South Sulawesi - Muchtar, M. Ilham; Erfandi AM; Fatkhul Ulum; Muchtar, Abdul Haris (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study explores the impact of Islamic legal literacy on promoting environmentally sustainable practices within the An-Nadzir community in Gowa, South Sulawesi. The primary aim of the research is to examine how knowledge of Islamic environmental ethics influences behaviors that contribute to environmental conservation. The study adopts a qualitative approach, gathering data through participatory observation, in-depth interviews, and a review of relevant literature. Interviews were conducted with members of the An-Nadzir community, while observations focused on their daily practices related to environmental sustainability. The findings suggest that a higher level of Islamic legal literacy significantly shapes the community’s adoption of environmentally friendly practices, including organic farming, waste management, and collective environmental efforts. The community’s leader plays a key role, as his example and teachings on Islamic stewardship (tadbīr al-khalīfah) have been central to promoting these practices. The research concludes that Islamic legal literacy fosters a cultural shift within the community, transforming environmental conservation into a shared responsibility. This cultural transformation highlights the potential of integrating religious teachings into practical environmental actions. Moreover, it offers valuable insights for other religious communities, showing how faith-based legal literacy can influence sustainable development. The study suggests that future research could examine similar cases in other religious contexts, helping to further explore the role of religious literacy in promoting sustainable practices across different communities.